Visitors' perceptions of the impact of spatial organization on wayfinding qualities in Kuala Lumpur Islamic Arts Museum - Bakhtiari, Mina (2012)
Museums are not only architectural spaces contain artefacts. Visitors come to museums for both entertainment and education and in other word: ‘edutainment’. Thus, every visitor has his/her own perception and interpretation of artefacts and it is the museum organization duty to enhance this perception as desirable as possible. Since perceiving the educational dimension of museums will be eased when people are moving and routing through the galleries and exhibitions, the way in which people are routed through the exhibitions can affect the overall perception. Since the plan configuration of Islamic Arts Museum Malaysia is listed as plans with less simplicity, so the wayfinding problem can occur in the museum and following this problem, visitors are not able to perceive the educational message of the museum through the exhibits. However according to the literature there is a number of factors that are likely to affect wayfinding inside an environment and this study is an effort to find the effect of these factors on visitors’ wayfinding inside the museums beside the effect of floor plan configuration. Method of inquiry applied in this study is survey; and the flow of the research starts with conducting a confirmation test in order to confirm the observed problems of Kuala Lumpur Islamic Arts Museum regarding wayfinding issue. Once the survey was chosen as the method, the survey questionnaire was designed in order to gather the data in the form of categorical questions; therefore, the method to analyze the data was chosen to be Chi-square analysis. The significant results of this study argue that between ‘spatial characteristics’ and ‘visitors’ demographic characteristics’ this is the latter that affects wayfinding inside the museum through constructing visitors’ expectation and consequently the perceived quality of the museum.